Perancangan dan Evaluasi User Experience Aplikasi Mobile Pembelajaran Online di Jurusan Sistem Informasi menggunakan Pendekatan Human- Centered Design dan TUXEL - Farha Rihhadatul Aisy; Herman Tolle; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Education 4.0 developed as a response to industry 4.0 is a learning process where students can carry out teaching and learning activities with the internet as the main pillar of its application. To respond to this, Information Systems Department from Brawijaya University needs new learning media for its students. The purpose of this study is to design the user experience of a mobile-based online learning application using Human-Centered Design approach. The stages begin with analyzing the context of use, analyzing user requirements, designing design solutions, evaluating the design, and design the improvement of the design solution. The evaluation was conducted with five respondents using TUXEL which consists of three dimensions, namely usability checking, pedagogical inspection, and user experience evaluation. Before completing the questionnaires, it is necessary to do a task definition and checklist matching according to the category on TUXEL. In the evaluation, it is found 23 usability inspection problems, 15 problems in pedagogical inspection, and the user experience evaluation indicate the codes: (1) Confusing; (2) Complicated; (3) Comfortable; (4) Supportive; (5) Efficient; (6) Practical; (7) Innovative; (8) Creative. It can be concluded that the application has a positive value in terms of user experience.